Crystalline morphologies at the surface of PET/PEN random copolymer films. Issue 5 (20th August 2019) - Shinotsuka, Kei; Assender, Hazel E.
Abstract: A series of PET (poly(ethylene terephthalate))/PEN (poly(ethylene 2, 6‐naphthalate)) copolyesters were synthesized by molten transesterification, and the surface crystallization behavior of their thin films investigated by atomic force microscope with an in situ heating stage. Force‐distance measurements detected a surface glass transition ( T gS ) of the copolymers several tens of degrees below their bulk glass transition ( T gB ) obtained by differential scanning calorimeter. The surface crystalline morphologies as a function of annealing temperature and film thickness were summarized as surface morphology diagrams. The surface crystallization temperature ( T cS ) was found to be several degrees lower than the bulk crystallization ( T cB ), and the films thinner than 100 nm showed significant increase in T cB . The lamellar crystalline morphology of copolymers with high randomness and short sequence length deviated from that of the homopolymers, reflecting the composition and degree of randomness. Highly random PET/PEN = 75/25 wt% copolymers exhibited unique lamellar curvature with arbitrary growth directions. Sharp boundaries between the crystals and amorphous suggested an absence of large amounts of rejected material at the growth front. In the case of copolymers with high randomness and short sequence length, no bulk crystallization morphology was observed even at 190°C, with the relatively thick surface crystalline layer totally covering the emergence of any bulk crystals. Abstract : Random copolymers of poly(ethylene terephthalate)/poly(ethylene 2, 6‐naphthalate) can show particular morphologies of crystals formed in the near‐surface region during annealing from an amorphous phase. The morphologies reflect the composition and randomness of the copolymer, and the constraint on the crystallizing region caused by the restricted thickness in thin films.